2022
DOI: 10.7753/ijcatr1105.1002
|View full text |Cite
|
Sign up to set email alerts
|

Development of CBT Integrated E-Module to Improve Student Literacy HOTS

Abstract: Generations in the 21st century must be prepared to have HOTS literacy competencies and skills. The application of HOTS literacy in the learning process makes students more resilient and able to solve their own problems. This study aims to develop an integrated CBT e-module to improve student literacy HOTS. The resulting e-module has met the valid criteria and has proven to be effective in increasing student literacy HOTS. Student responses to the resulting e-modules are also very positive because the e-module… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The most important thing in 21st century education is to encourage students to have a deep knowledge base and understanding to be able to become life-long learners. Thus, the education system needs to consider a number of aspects that are domains in 21st century education [4]. 21st century learning is required to be technology-based to balance the demands of the millennial era with the aim that later students will become accustomed to 21st century life skills.…”
Section: Introductionmentioning
confidence: 99%
“…The most important thing in 21st century education is to encourage students to have a deep knowledge base and understanding to be able to become life-long learners. Thus, the education system needs to consider a number of aspects that are domains in 21st century education [4]. 21st century learning is required to be technology-based to balance the demands of the millennial era with the aim that later students will become accustomed to 21st century life skills.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is related to the provision of learning materials and materials that are not widely accessible without being limited by distance and time constraints [1]. In addition, the development of modernization and globalization of the 21st century has also had a tremendous impact in all fields including education [2] Since the advent of optical cable technology and web browsers, the flow of information spread around the world has become increasingly out of control and has resulted in the socalled 'digital information explosion'. Through a search engine, one can easily find the desired reference material in real time at a very, very low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Problem Based Learning (PBL) is one of the innovative learning models that can provide active learning conditions for students. The PBL model prepares lessons for critical and analytical thinking, as well as for finding and using learning resources [11]. The Problem Based Learning (PBL) learning model has been studied by several previous researchers and has been proven to improve student learning outcomes [12], including: concluded that 1) there is an increase in students' creative thinking skills using the PBL model, 2) there is an increase in students' creative thinking skills.…”
Section: Introductionmentioning
confidence: 99%